Duration of playing mobile legends on the incidence of De Quervain syndrome among e-sport players - Putu Premanatara Pradnyadewi; Anak Ayu Nyoman Trisna Narta Dewi; Nila Wahyuni; Made Hendra Satria Nugraha (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: The development of e-sports in Indonesia is influenced by favorable economic aspects such as commercial and marketing activities, but it also poses physiological problems such as game addiction, physical injuries, and social disorders. This study analyzed the relationship between the duration of playing mobile legends and de Quervain's syndrome (DQS) incidence in e-sport players. Methods: This study used a descriptive-analytic cross-sectional approach. The inclusion criteria were mobile legend esports players who had been in the game for at least one year, while the exclusion criteria were injuries in the wrist. The sampling technique used was total sampling, with the research location in Denpasar City, Bali. Data was collected in April 2023 using a personal data questionnaire, and a sample with DQS was determined using the Finkelstein test. The study's 150 subjects were analyzed using IBM SPSS 26 software. Results: The results of data analysis and hypothesis test showed that there was a significant association between the duration of playing mobile legends and the incidence of DQS among e-sport players in the city of Denpasar (p= 0.001) Conclusion: Playing mobile legends for more than 2.25 hours a day potentially increases the risk of DQS, while shorter playing durations correlate with lower risks.